Role of General Principles of AGAD Tantra in Diagnosis and Management of Toxicological Conditions – A Comprehensive Review - Kumar, Pawan; Namewar, Prasad (Journal of Neonatal Surgery, 2025)
Agad Tantra, a specialized branch among the eight clinical divisions of Ayurveda, focuses on the study, diagnosis, and management of poisons (Visha) originating from animate, inanimate, and artificial sources. In the contemporary era, the burden of toxicological conditions has surged significantly due to increased exposure to environmental pollutants, pesticide residues, adulterated food, heavy metals, and pharmaceutical drugs. These toxic agents contribute to a wide spectrum of acute and chronic disorders, necessitating integrative approaches to their diagnosis and management.Classical Ayurvedic texts meticulously describe the origin, classification, symptomatology, and therapeutic modalities related to various toxins through concepts such as Visha Utpatti (origin of toxins), Visha Lakshana (clinical features of poisoning), and Shodhana-Upashaya (detoxification and treatment). The principles of Dushi Visha, Garavisha, and Jangama-Sthavara Visha in Agad Tantra offer profound insight into the understanding of slow-acting, compound, and natural poisons, respectively. These principles can be reinterpreted in the context of modern toxicology, providing a foundation for early detection, differential diagnosis, and individualized detoxification therapies.Therapeutic measures in Agad Tantra include the use of Agada Yogas (antidotal formulations), Shodhana Chikitsa (purificatory therapies like Vamana, Virechana, Basti), and Rasayana (rejuvenation) for recovery and immunity enhancement. This review aims to consolidate the general principles of Agad Tantra and analyze their applicability in modern clinical toxicology, proposing a synergistic model that blends ancient wisdom with contemporary scientific insights. Such integrative approaches have the potential to offer holistic, safe, and sustainable solutions in managing toxicological challenges of the present age